Deeper, wider and more competitive? Monetary integration, Eastern enlargement and competitiveness in the European Union - Gianmarco Ottaviano; Daria Taglioni; Filippo di Mauro (European Central Bank (ECB), 2007)
What determines a country's ability to compete in international markets? What fosters the global competitiveness of its firms? And in the European context, have key elements of the EU strategy such as EMU and enlargement helped or hindered domestic firms' competitiveness in local and global markets? We address these questions by calibrating and simulating a conceptual framework that, based on Melitz and Ottaviano (2005), predicts that tougher and more transparent international competition drives less productive firms out the market, thereby increasing average productivity as well as reducing average prices and mark-ups. The model also predicts a parallel reduction of price dispersion within sectors. Our conceptual framework allows us to disentangle the effects of technology and freeness of entry from those of accessibility (i.e. the ease for local firms to reach local and foreign consumers). On the one hand, by controlling for the impact of trade frictions, we are able to construct an index of 'revealed competitiveness', which would drive the relative performance of countries in an ideal world in which all faced the same barriers to international transactions. On the other hand, by focusing on the role of accessibility while keeping 'revealed competitiveness' as given, we are able to evaluate the impacts of EMU and enlargement on the competitiveness of European firms. We find that EMU positively affects the competitiveness of firms located in participating economies. Enlargement has, instead, two contrasting effects. It improves the accessibility of EU members but it also increases substantially the relative importance of unproductive competitors from Eastern Europe.
Keywords: F12; R13; 330; competitiveness; European Integration; firm-level data; gains from trade; total factor productivity; Internationaler Wettbewerb; Eurozone; EU-Mitgliedschaft; Außenhandelsgewinn; Produktivität; EU-Staaten